2021
DOI: 10.1093/femsec/fiab031
|View full text |Cite
|
Sign up to set email alerts
|

Root exposure to apple replant disease soil triggers local defense response and rhizoplane microbiome dysbiosis

Abstract: A soil column split-root experiment was designed to investigate the ability of apple replant disease (ARD) causing agents to spread in soil. ‘M26’ apple rootstocks grew into a top layer of Control soil, followed by a barrier-free split-soil layer (Control soil/ARD soil). We observed a severely reduced root growth, concomitant with enhanced gene expression of phytoalexin biosynthetic genes and phytoalexin content in roots from ARD soil, indicating a pronounced local plant defense response. Amplicon sequencing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…ARD is a soil-borne disease caused by a complex of the imbalance of nutrient elements, soil property deterioration, allelopathy accumulation, and shifts in bacterial and fungal communities . Biotic factors, including explosive reproduction of harmful fungi and the deterioration of the microbial community structure after long-term planting of fruit trees, are recognized as the dominant factor resulting in ARD. , In recent years, broad-spectrum fumigants, such as methyl bromide, which indiscriminately kill most soil microorganisms, have favorable effects in controlling ARD.…”
Section: Introductionmentioning
confidence: 99%
“…ARD is a soil-borne disease caused by a complex of the imbalance of nutrient elements, soil property deterioration, allelopathy accumulation, and shifts in bacterial and fungal communities . Biotic factors, including explosive reproduction of harmful fungi and the deterioration of the microbial community structure after long-term planting of fruit trees, are recognized as the dominant factor resulting in ARD. , In recent years, broad-spectrum fumigants, such as methyl bromide, which indiscriminately kill most soil microorganisms, have favorable effects in controlling ARD.…”
Section: Introductionmentioning
confidence: 99%
“…However, a relationship between ARD severity and the production of terpenoid phytoalexins in the plant has not been observed to date. Several studies on ARD demonstrated remarkably higher contents of biphenyl and dibenzofuran phytoalexins in plants cultivated in ARD soils compared to disinfected ARD soils ( Winkelmann et al, 2019 ; Reim et al, 2020 ; Rohr et al, 2020b ; Balbin-Suarez et al, 2021 ; Busnena et al, 2021 ). However, Reim et al (2020) showed that the genes coding for biosynthesis of these phytoalexins were more strongly induced in the susceptible rootstock ‘M9’ than in the ARD tolerant genotype Mr5, indicating that these phytoalexin compounds do not help against ARD.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is most harmful to young replanted trees, and it can reduce the growth of trees, increase the susceptibility of trees to diseases, discolor roots, result in root tip necrosis, and reduce root biomass, which can ultimately lead to plant death within the first growing season. Furthermore, the yield and quality of fruit trees more than 20 years old is decreased in plants with ARD, and death can occur in severe cases ( Mazzola and Manici, 2012 ; Yim et al, 2020 ; Balbín-Suárez et al, 2021 ). An increasing number of studies have shown that biotic factors are the main factors that cause ARD, including nematodes ( Pratylenchus spp.…”
Section: Introductionmentioning
confidence: 99%